2020
DOI: 10.3390/nu12071962
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Lixisenatide on Energy Intake in Healthy Subjects and Patients with Type 2 Diabetes: Relationship to Gastric Emptying and Intragastric Distribution

Abstract: Glucagon-like peptide-1 receptor agonists induce weight loss, which has been suggested to relate to the slowing of gastric emptying (GE). In health, energy intake (EI) is more strongly related to the content of the distal, than the total, stomach. We evaluated the effects of lixisenatide on GE, intragastric distribution, and subsequent EI in 15 healthy participants and 15 patients with type 2 diabetes (T2D). Participants ingested a 75-g glucose drink on two separate occasions, 30 min after lixisenatide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Individual patterns of gastrointestinal symptoms were found and are probably attributable to the pharmacological differences of liraglutide and lixisenatide. We find an association between prolonged gastric emptying and the reduction in energy intake after GLP‐1 RA treatment, in contrast to a previous publication 48 . This may just be an association, indicating GLP‐1 receptor target engagement leading to diverse biological responses.…”
Section: Discussioncontrasting
confidence: 98%
“…Individual patterns of gastrointestinal symptoms were found and are probably attributable to the pharmacological differences of liraglutide and lixisenatide. We find an association between prolonged gastric emptying and the reduction in energy intake after GLP‐1 RA treatment, in contrast to a previous publication 48 . This may just be an association, indicating GLP‐1 receptor target engagement leading to diverse biological responses.…”
Section: Discussioncontrasting
confidence: 98%
“…It is possible that a reduced effect of long‐ versus short‐acting GLP‐1 RAs to slow gastric emptying may contribute to the lower incidence of GI AEs with long‐acting GLP‐1 RAs; however, it has recently been demonstrated that exenatide once weekly slows gastric emptying significantly even at steady‐state concentrations 38 . Moreover, the suppression of energy intake by lixisenatide is not related to slowing of gastric emptying or changes in intragastric meal distribution 39 . It is notable that recent updates to titration schemas for weekly GLP‐1 RA therapies have incorporated extended titration steps for up to 4 weeks to help minimize GI AEs 40–42 …”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, the suppression of energy intake by lixisenatide is not related to slowing of gastric emptying or changes in intragastric meal distribution. 39 It is notable that recent updates to titration schemas for weekly GLP-1 RA therapies have incorporated extended titration steps for up to 4 weeks to help minimize GI AEs. [40][41][42] The strengths of our analysis include a comprehensive literature search based on standardized prespecified search criteria, with confounding reduced by using only studies with the recommended titrated dose of each GLP-1 RA.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…The weight loss achieved with subcutaneous semaglutide is independent of gastrointestinal adverse events though other studies confirm that both weekly and oral semaglutide retard gastric emptying [ 154 , 189 , 190 ]. Nevertheless, weight loss associated with GLP-1 receptor agonists may be independent of gastric motor changes and related to central appetite regulation [ 191 , 192 , 193 ].…”
Section: Treatments Of Obesity and Their Effects On Gastric Sensory And Motor Functionsmentioning
confidence: 99%